2018
DOI: 10.1186/s13054-018-2076-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of neutropenia on mortality of critically ill cancer patients: results of a meta-analysis on individual data

Abstract: BackgroundThe study objective was to assess the influence of neutropenia on outcome of critically ill cancer patients by meta-analysis of individual data. Secondary objectives were to assess the influence of neutropenia on outcome of critically ill patients in prespecified subgroups (according to underlying tumor, period of admission, need for mechanical ventilation and use of granulocyte colony stimulating factor (G-CSF)).MethodsData sources were PubMed and the Cochrane database. Study selection included arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 64 publications
2
27
0
4
Order By: Relevance
“…In an unselected population of neutropenic critically ill patients, several recent studies failed to demonstrate any impact of neutropenia, neutropenia duration, or resolution of neutropenia on the outcome of critically ill cancer patients [1,43,44]. In a large meta-analysis, it was demonstrated in more than 1700 neutropenic critically ill patients that neutropenia was independently associated with poor outcome despite a meaningful survival [45]. Nevertheless, certain infections together with neutropenia are associated with extremely poor outcome or high mortality (e.g., Fusarium infection [46]).…”
Section: Screening Criteria For Sepsis and Performance Improvementmentioning
confidence: 99%
“…In an unselected population of neutropenic critically ill patients, several recent studies failed to demonstrate any impact of neutropenia, neutropenia duration, or resolution of neutropenia on the outcome of critically ill cancer patients [1,43,44]. In a large meta-analysis, it was demonstrated in more than 1700 neutropenic critically ill patients that neutropenia was independently associated with poor outcome despite a meaningful survival [45]. Nevertheless, certain infections together with neutropenia are associated with extremely poor outcome or high mortality (e.g., Fusarium infection [46]).…”
Section: Screening Criteria For Sepsis and Performance Improvementmentioning
confidence: 99%
“…The role of neutrophils in cancer development remains controversial [34,35]. There have been few reports on the correlation between the NC and metastasis in osteosarcoma patients [36][37][38]. A pretreatment NC ≥6400/µL in osteosarcoma patients was reported to be associated with the 5-year lung metastasis-free survival (65% vs. 44%, in comparison with an NC <6400/µL).…”
Section: Discussionmentioning
confidence: 99%
“…Granulocyte-macrophage colony stimulating factor (GM-CSF) showed no detectable effect in recurrent pulmonary metastasis in osteosarcoma [36]. However, a meta-analysis of the in uence of neutropenia on cancer patients revealed that neutropenia in patients without Granulocyte colony stimulating factor (G-CSF) administration was independently associated with a poor outcome, compared with patients receiving G-CSF administration during chemotherapy [38]. Various stimuli in the tumor microenvironment have been reported to result in the differentiation of neutrophils into either an antitumor or pro-tumor phenotype [39].…”
Section: Discussionmentioning
confidence: 99%
“…Konsekuensi klinis neutropenia ini dapat menyebabkan gagal napas akut ataupun sepsis sehingga netropenia menjadi faktor risiko independen yang menyebabkan hasil yang buruk pada perawatan di ruang ICU. 16 Distribusi subjek berdasarkan limfosit terhadap mortalitas terdapat perbedaan rerata limfosit terhadap mortalitas. Penelitian tentang hitung jenis limfosit mendapatkan bahwa hitung limfosit yang rendah berhubungan dengan mortalitas yang lebih tinggi dan hasil akhir kejadian kardiovaskular yang buruk pada pasien dengan nyeri dada, penyakit jantung koroner stabil, angina pektoris tidak stabil dan gagal jantung kronik.…”
Section: Pendahuluanunclassified